Photoembossing of surface relief structures in polymer films for biomedical applications. Issue 2 (2nd August 2013) - Hughes‐Brittain, Nanayaa F.; Qiu, Lin; Wang, Wen; Peijs, Ton; Bastiaansen, Cees W.M.
Abstract Photoembossing is a technique used to create relief structures using a patterned contact photo‐mask exposure and a thermal development step. Typically, the photopolymer consists of a polymer binder and a monomer in a 1/1 ratio together with a photo‐initiator, which results in a solid and non‐tacky material at room temperature. Here, new mixtures for photoembossing are presented which are potentially biocompatible. Poly(methyl methacrylate) is used as a polymer binder and two different acrylate monomers trimethylolpropane ethoxylate triacrylate (TPETA) and dipentaerythritol penta‐/hexa‐acrylate (DPPHA) are tested. PMMA‐TPETA had a higher surface relief features. Biocompatibility is evaluated by culturing human umbilical vein endothelial cells (HUVECs) on films of these photopolymer blends. PMMA with TPETA and PMMA‐DPPHA films showed enhanced cell adhesion compared to PMMA. The cells also showed alignment on surface textured films with the highest degree of alignment on films with 20 μm pitch and 2 μm height. This study shows that photoembossing is a feasible method to produce surface textures on films that can be adopted in the field of tissue engineering to promote cell adhesion and alignment. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 214–220, 2014.